1997
DOI: 10.1111/j.2044-835x.1997.tb00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐direction detection: A dissociation between geometric and joint attention skills in autism

Abstract: This study examined differences between children with autism and control children in the ability to follow another person's direction of gaze. In Expt 1, children with autism, Down syndrome and normally developing children were given two tasks. The gaze monitoring task (GMT) measured the child's spontaneous tendency to follow gaze direction in response to another person's change of head and eye movement. The visual perspective taking task (VPT) measured the child's ability to compute and report what the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
192
1
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(206 citation statements)
references
References 21 publications
12
192
1
1
Order By: Relevance
“…Therefore, the findings are still preliminary to suggest that the impairments are specific to children with autism. The finding of VPT impairment in children with autism is in line with some previous studies (Hamilton, et al, 2009;Reed, 2002;Warreyn, et al, 2005;Yirmiya et al, 1994), but contradicts the findings of others (Baron-Cohen, 1989;Hobson, 1984;Leekam et al, 1997;Leslie & Frith, 1988;Reed & Peterson, 1990;Tan & Harris, 1991). One of the possible reasons for this inconsistency is the different designs of tasks.…”
Section: Discussionsupporting
confidence: 34%
“…Therefore, the findings are still preliminary to suggest that the impairments are specific to children with autism. The finding of VPT impairment in children with autism is in line with some previous studies (Hamilton, et al, 2009;Reed, 2002;Warreyn, et al, 2005;Yirmiya et al, 1994), but contradicts the findings of others (Baron-Cohen, 1989;Hobson, 1984;Leekam et al, 1997;Leslie & Frith, 1988;Reed & Peterson, 1990;Tan & Harris, 1991). One of the possible reasons for this inconsistency is the different designs of tasks.…”
Section: Discussionsupporting
confidence: 34%
“…In terms of eye-gaze direction discrimination, Leekam, Baron-Cohen, Perrett, Milders and Brown (1997) suggested that individuals with ASD are able to determine the direction of gaze relatively accurately; conversely Ashwin, Wicker and Baron-Cohen (2006) suggested that gaze direction perception is abnormal in individuals with ASD. As individuals with ASD often do not attend to the global content of stimuli unless prompted (e.g., Happé & Frith, 2006) and gaze cues have been shown to be voluntary rather than reflexive in individuals with ASD (Ristic et al, 2005) we predicted that eye-gaze direction would not cue individuals with ASD at all when searching for an object that is appearing/disappearing as it was not directly relevant to the task, hence no differences between the Straight Gaze conditions and the Gaze Object conditions were predicted for spotting the disappearing objects in any of the three locations.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that both children (Senju et al, 2003) and adults (Howard et al, 2000) with autism have difficulties in recognising gaze stimuli with an eye contact among serially presented averted-gaze stimuli. That the deficit is specifically related to the processing of eye contact is supported by the findings that individuals with autism can make overt discriminations of where other people are looking (Baron-Cohen et al, 1995;Kyllia¨inen & Hietanen, 2004;Leekam, Baron-Cohen, Perrett, Milders, & Brown, 1997;Tan & Harris, 1991) and that seeing of another person's averted gaze direction triggers an automatic shift of visual attention comparably in the clinical and control groups (Chawarska, Klin, & Volkmar, 2003;Kyllia¨inen & Hietanen, 2004;Senju, Tojo, Dairoku, & Hasegawa, 2004;Swettenham, Condie, Campbell, Milne, & Coleman, 2003).…”
mentioning
confidence: 89%